The Measurement Analysis of Parent-grandparent as Educator Questionnaire (Parent Version) - Yusuf, Muhammed (International Review of Management and Marketing, 2016)
This paper examined the claims for validity and reliability of parent-grandparent as educator questionnaire (PGEQ). The PGEQ is a multi-dimensional instrument which is capable of reliably measuring parents and grandparents’ religious thought, superstition, culture, morality, socialization, economy, education, language, internationalization, and skill that they pass on to children and grandchildren. A sample of 338 were randomly selected from three Malaysia cities. The researcher applied Principal Components Analysis, Confirmatory Factor Analysis, and Cronbach’s alpha to test validity and reliability of the PGEQ. The analysis results suggest that the PGEQ is a multi-dimensional instrument which reliably measured ten-factor structure with a total number of 63 validate and reliable items. The PCA extracted factors accounted for 75.7 percent of total variance explained. Interestingly, the degree of inter-correlation among the items of the PGEQ also reached a satisfactory level. The CFA indicates the assessment result of within and between the validity of indicators of the 10-factor model, Ï‡2 (9) =27. 560, CFI=0. 986, TLI=0. 929, RMSEA=0. 078, GFI=0. 985 and AGFI=0. 906. These findings established a satisfactory measurement model fit for the PGEQ. The study not only singnificantly contributes to on going parental instrument development, but also addes to the development of a psychometrically sound instrument to conduct diagnostic assessments on parents, grandparents, and childminders’ contributions to children’s upbringing in a wide range. Keywords: Parent-grandparent as Educator Questionnaire, Questionnaire, Parent-grandparent, Educator JEL Classifications: A10, A20, A30